Collective action for the conservation of on-farm genetic diversity in a center of crop diversity: an assessment of the role of traditional farmers’ networks - Badstue, Lone Bech; Bellon, Mauricio R.; Berthaud, Julien; Ramírez, Alejandro; Flores, Dagoberto; Juárez, Xóchitl; Ramírez, Fabiola (International Food Policy Research Institute, 2005)
This project explored the possible role of collective action among small-scale farmers in managing and maintaining genetic resources in a center of crop diversity. It focused on the local institutions that ensure the supply of seed of diverse maize landraces to small-scale farmers in the Central Valleys of Oaxaca, Mexico. The key hypothesis was that the medium-to-long-term supply of a diverse set of varieties to any individual small-scale maize farmer depends on an agreement among a group of farmers to manage and supply the seed of these landraces to each other, if the need arises, and that this constitutes a form of collective action. Six communities were studied, three of them in-depth. Methodologies used included in-depth semi-structured interviews with key informants, focus group discussions, and a tracer study—following the flows of seed among different farmers. The results show that, while there is a well-developed local seed supply system based on sets of social relationships and involving multiple types of transactions, there is no evidence of collective action. Most farmers rely on and prefer to select and save seed from their own harvests. There are seed flows, however, and most seed transactions take place among people with social links, but not within a well-defined group. There are no specialized suppliers of seed, either individuals or groups. Most transactions are bilateral and while the most common transaction is the sale and purchase of seed, this is not done for profit but out of a sense of moral obligation. The system is based on the creation of trust, which is needed because seed is not transparent—that is, it is not possible to fully predict the plant phenotype that may result from a given seed simply by looking at the seed. Farmers demand different types of maize and they believe that there is a strong genotype-by-environment interaction, hence “foreign” maize types may not be appropriate for them. At the same time, farmers also find occasional experimentation beneficial and believe that they can slowly modify the characteristics of “foreign” landraces. In this system, there are strong incentives to be conservative, but also to try new landraces and experiment. The local seed system of these farmers is resilient but able to innovate as well. Interventions to support the conservation of landraces on farm, based on specialized networks for seed that rely on collective action, may not work.